2016
DOI: 10.1097/mph.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Gene Expression of Survivin, its Antiapoptotic Variants, and Targeting Survivin In Vitro for Therapy in Retinoblastoma

Abstract: Apoptosis is a natural process regulated by apoptotic and antiapoptotic molecules. We investigated mRNA expression of survivin and its splice variants, along with B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X (Bax), in a cohort of 20 retinoblastoma (RB) tumors by real-time polymerase chain reaction. We hypothesized a correlation between the Bcl-2/Bax and survivin splice variants and also that expression of these would be associated with clinicopathologic features of tumors. The Bcl-2 expression was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, the expression of Bcl-2, another anti-apoptotic factor, was relatively higher in emphysematous smokers than that in emphysematous patients with COPD. Studies have confirmed Bcl-2 expression does not correlate with Survivin expression, which may also explain the relatively higher expression of Survivin in patients with COPD 30 .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the expression of Bcl-2, another anti-apoptotic factor, was relatively higher in emphysematous smokers than that in emphysematous patients with COPD. Studies have confirmed Bcl-2 expression does not correlate with Survivin expression, which may also explain the relatively higher expression of Survivin in patients with COPD 30 .…”
Section: Discussionmentioning
confidence: 98%
“…In the continued study on genomics and pathogenesis of RB, the regulation and intervention targeting the key gene of RB has become a new strategy for RB treatment. Studies have shown that B-cell lymphoma 2 (Bcl-2) and Survivin (Svv) mRNAs are overexpressed in RB cells, suggesting that these two mRNAs might be promising therapeutic targets. , In particular, the eye offers certain anatomical advantages as a target tissue, which is conducive to the development of multifunctional diagnostic nanocontrast agents combining anti-RB gene therapeutic agents with multimodal imaging technology. Currently, the agents mainly used for RB gene therapy are small interfering RNA (siRNA). , However, compared to DNA gene therapeutic agents, RNA is less stable and exhibits lower enzymatic degradation resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that B-cell lymphoma 2 (Bcl-2) and Survivin (Svv) mRNAs are overexpressed in RB cells, suggesting that these two mRNAs might be promising therapeutic targets. 3,4 In particular, the eye offers certain anatomical advantages as a target tissue, which is conducive to the development of multifunctional diagnostic nanocontrast agents combining anti-RB gene therapeutic agents with multimodal imaging technology. Currently, the agents mainly used for RB gene therapy are small interfering RNA (siRNA).…”
Section: ■ Introductionmentioning
confidence: 99%